2018
DOI: 10.1002/pat.4379
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the oxygen barrier property of polypropylene nanocomposites

Abstract: A nanocomposite consisting of polypropylene (PP)/nanoclay (montmorillonite) was prepared by means of a melt-compounding process with the use of a twin-screw extruder. Because of the complex dispersion of polar and hydrophilic clays that have many cations in the nonpolar and hydrophobic PP, amino-silane was introduced to modify the surface of the clays. Also, to improve the compatibility of the modified nanoclay with PP, a PP-graft-maleic anhydride was used as a compatibilizer. From Fourier transform infrared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Moreover, the permeability of N2V and N5V is also lower than most results from the literature for PP/PPg NCs prepared with clays similar to the oMt used in this study and PPg/oMt ratios between 5:1 and 2:5. In the literature, values up to 20% and 40% lower than the corresponding PP are reported when 2 and 5 wt% clay are used, respectively 41,42,44–46 . One factor to take into account when analyzing the permeability of the NCs from Procedure V is that the PPg/oMt ratio surely decreases with clay concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the permeability of N2V and N5V is also lower than most results from the literature for PP/PPg NCs prepared with clays similar to the oMt used in this study and PPg/oMt ratios between 5:1 and 2:5. In the literature, values up to 20% and 40% lower than the corresponding PP are reported when 2 and 5 wt% clay are used, respectively 41,42,44–46 . One factor to take into account when analyzing the permeability of the NCs from Procedure V is that the PPg/oMt ratio surely decreases with clay concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Gas permeability of NCs is a property that, for given ambient conditions, is mainly affected by crystallinity level of polymeric matrix, type and quantity of nano‐clay and compatibilizer, clay/polymer adhesion quality, and clay degree of disaggregation. With respect to clay and compatibilizer concentrations, in general it has been observed that oxygen permeability decreases as they augment 41,42,44–46 . Moreover, for a given filler content, the permeability reduction is higher as the degree of disaggregation of the clay and/or polarity and crystallinity of the matrix get larger.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks are assigned to the basal spacing of d 001 and d 002 , respectively. The basal spacing of d 001 is considered as an indicator of the interlayer distance between the silicate crystal plates of the nanoclay structure that can be calculated following the Bragg’s equation [46].…”
Section: Resultsmentioning
confidence: 99%
“…[19] To deal with the nanofiller dispersion issue, a compatibilizer can be added to the polymer/HNT blend. [20,21] The impact of nanoparticles on the mechanical properties and gas permeability of polymer blends has been extensively studied in packaging applications. For example, Kubade et al [22] observed that by adding surface-modified HNTs to polypropylene (PP)/acrylonitrile butadiene styrene blends, significant improvements in the tensile strength (by ≈5 MPa) and tensile modulus (by ≈160 MPa) of the polymer blend sheet were achieved.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] To deal with the nanofiller dispersion issue, a compatibilizer can be added to the polymer/HNT blend. [ 20,21 ] The impact of nanoparticles on the mechanical properties and gas permeability of polymer blends has been extensively studied in packaging applications. For example, Kubade et al.…”
Section: Introductionmentioning
confidence: 99%